Molecular classifications of gastric cancer and their clinical potential - M. V. Nemtsova; A. D. Molchanov; E. B. Kuznetsova; I. V. Bure (Успехи молекулярной онкологии, 2024)
Gastric cancer if the 5th most common oncological disease in the world and one of the leading causes of death associated with this pathology. In clinical practice, the Lauren classification is widely used for gastric cancer characterization, but it does not provide accurate information on tumor progression and does not allow to select the optimal therapeutic approach. More modern tumor typologies, for example proposed by the The Cancer Genome Atlas (TCGA) and the Asian Cancer Research Group (ACRG), are based on profiling of molecular changes in the tumor genome. Currently, several new classifications exist dividing gastric cancer into groups depending on response to different treatment, for example, checkpoint inhibitors or therapy based on activity of pathological pathways associated with immunity, DNA repair, oncogenic and stromal signatures. The proposed typologies improve diagnosis and treatment of this pathology. The review describes currently available classifications of gastric tumors and considers their practical potential.